Numerical modeling of experimental human fibrous cap delamination. (June 2016) - Leng, Xiaochang; Davis, Lindsey A.; Deng, Xiaomin; Sutton, Michael A.; Lessner, Susan M.
Abstract: Fibrous cap delamination is a critical process during the rupture of atherosclerotic plaque, which often leads to severe life-threatening clinical consequences such as myocardial infarction or stroke. In this study a finite element modeling and simulation approach is presented that enables the study of fibrous cap delamination experiments for the purpose of understanding the fibrous cap delamination process. A cohesive zone model (CZM) approach is applied to simulate delamination of the fibrous cap from the underlying plaque tissue. A viscoelastic anisotropic (VA) model for the bulk arterial material behavior is extended from existing studies so that the hysteresis phenomenon observed in the fibrous cap delamination experiments can be captured. A finite element model is developed for the fibrous cap delamination experiments, in which arterial layers (including the fibrous cap and the underlying plaque tissue) are represented by solid elements based on the VA model and the fibrous cap-underlying plaque tissue interface is characterized by interfacial CZM elements. In the CZM, the delamination process is governed by an exponential traction-separation law which utilizes critical energy release rates obtained directly from the fibrous cap delamination experiments. A set of VA model parameter values and CZM parameter values is determined based on values suggested in the literature and through matching simulation predictions of the load vs. load-point displacement curve with one set of experimental measurements. Using this set of parameter values, simulation predictions for other sets of experimental measurements are obtained and good agreement between simulation predictions and experimental measurements is observed. Results of this study demonstrate the applicability of the viscoelastic anisotropic model and the CZM approach for the simulation of diseased arterial tissue failure processes.